2015
DOI: 10.1160/th14-12-1043
|View full text |Cite
|
Sign up to set email alerts
|

Genetic determinants of tissue factor pathway inhibitor plasma levels

Abstract: Tissue factor pathway inhibitor (TFPI) impedes early stages of the blood coagulation response, and low TFPI plasma levels increase the risk of thrombosis. TFPI plasma levels are heritable, but specific genetic determinants are unclear. We conducted a comprehensive review of genetic risk factors for TFPI plasma levels and identified 26 studies. We included 16 studies, as well as results from two unpublished genome-wide studies, in random effects meta-analyses of four commonly reported genetic variants in TFPI a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 70 publications
0
16
1
Order By: Relevance
“…This is supported by Th− patients having a significantly higher TFPI/TF ratio, and indeed by the absence of a thrombosis history in all individuals with a ratio >0.7. The reasons behind some BS patients having a relatively low level of MP-associated TFPI compared to MP-associated TF are unclear, but could include differential synthesis of TF and TFPI by activated monocytes24, TFPI degradation by leukocyte-derived serine proteases and/or reactive oxygen species4546 and the influence of genetic variants of TFPI on plasma levels47.…”
Section: Discussionmentioning
confidence: 99%
“…This is supported by Th− patients having a significantly higher TFPI/TF ratio, and indeed by the absence of a thrombosis history in all individuals with a ratio >0.7. The reasons behind some BS patients having a relatively low level of MP-associated TFPI compared to MP-associated TF are unclear, but could include differential synthesis of TF and TFPI by activated monocytes24, TFPI degradation by leukocyte-derived serine proteases and/or reactive oxygen species4546 and the influence of genetic variants of TFPI on plasma levels47.…”
Section: Discussionmentioning
confidence: 99%
“…Previous candidate gene studies of TFPI plasma levels have focused on hemostatic‐ and lipid‐related genes (reviewed in Dennis et al., ). Increasingly, however, genes with no previously known roles in clotting are being implicated in VTE (Antoni et al., ), arterial thrombosis, and thrombosis‐related phenotypes (Antoni et al., ; Morange et al., ; Rocanin‐Arjo et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…Up to 52% of the variability in TFPI plasma levels is attributable to genetics (Almasy et al., ; Bladbjerg et al., ; Dennis et al., ; Warren et al., ), but few genes have been implicated. Most studies have been of candidate coagulation genes ( TFPI , PROS1 , F5 ), yet variants in these genes explained little of TFPI plasma level variability (Dennis, Kassam, Morange, Tregouet, & Gagnon, ), and in vitro and mouse models suggested that genes outside of the hemostatic pathway may be important (Lupu, Zhu, Popescu, Wren, & Lupu, ; Sanchez‐Solana, Motwani, Li, Eswaran, & Kumar, ). Genome‐wide linkage studies of TFPI plasma levels have been reported (Almasy et al., ; Dennis et al., ), and fine mapping of the most significant linkage signal identified three SNPs 25.1 Mb upstream of TFPI associated with TFPI plasma level variability and VTE risk (Dennis et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…While it is possible that it is a false positive, it could also have a population specific effect or an interaction with environmental factor(s). Interestingly, the expression of TFPI (Tissue Factor Pathway Inhibitor) has been linked to risk of thrombosis and heart disease previously (52) and a coding SNP in this region (rs7586970 or TFPI N221S within 500 KB) has been shown to be associated with total plasma TFPI levels (53). The unweighted and weighted pvalues for the crossover SNPs along with the association results from some independent studies are summarized in Table 2.…”
Section: Gwas Of Coronary Artery Disease (Cad): Summary Data On Coronmentioning
confidence: 99%